The Presynaptic Protein Mover Is Differentially Expressed Across Brain Areas and Synapse Types - Wallrafen, Rebecca; Dresbach, Thomas (Frontiers in Neuroanatomy, 2018)
The assembly and function of presynaptic nerve terminals relies on evolutionarily conserved proteins. A small number of presynaptic proteins occurs only in vertebrates. These proteins may add specialized functions to certain synapses, thus increasing synaptic heterogeneity. Here, we show that the vertebrate-specific synaptic vesicle protein mover is differentially distributed in the forebrain and cerebellum of the adult mouse. Using a quantitative immunofluorescence approach, we compare the expression of mover to the expression of the general synaptic vesicle marker synaptophysin in sixteen brain areas. We find that mover is particularly abundant in the septal nuclei, ventral pallidum, amygdala and hippocampus. Within the hippocampus, mover is predominantly associated with excitatory synapses. Its levels are low in layers that receive afferent input from the entorhinal cortex, and high in layers harboring intra-hippocampal circuits. In contrast, mover levels are high in all nuclei of the amygdala, and mover is associated with inhibitory synapses in the medioposterior amygdala. Our data reveal a striking heterogeneity in the abundance of mover on three levels, i.e. between brain areas, within individual brain areas and between synapse types. This distribution suggests a role for mover in providing specialization to subsets of synapses, thereby contributing to the functional diversity of brain areas.